L'avvenire dei figli dei matrimoni falliti dipende dal tuo voto : al referendum rispondi no (PCI (Italian Communist Party), 1974)
All text; portrait of boy in pointillism Poster from the Italian Communist Party campaigning for the No vote in the Italian divorce referendum, held in May, 1974 PO-0273